Improving English language skills for human resources at CV. Langgeng Jaya, Jombang - Sheila Wijayanti; Selvina Ulita Napitupulu (Universitas Muhammadiyah Magelang, 2024)
Globalization necessitates the world of work to have proficient Human Resources (HR), particularly in foreign language skills. English, being an internationally utilized foreign language, serves as an additional advantage in the professional domain. This activity aims to ensure that HR at CV. Langgeng Jaya, Jombang, possesses basic English skills, especially in the vocabulary related to the transportation industry. The method employed for this activity includes observation, socialization, drilling, practice, and question-and-answer sessions (interviews) with HR. The results of this activity indicate an enhancement in the basic knowledge of English related to the transportation sector among HR at CV. Langgeng Jaya, Jombang. The percentage reveals that 82% of human resources now comprehend basic English, compared to the initial 40% from a total of 50 people. It can be concluded that there has been an improvement in HR skills for engaging in conversations using basic English.